Fragile Partnership to Sustainable Alliance: Rapid-Response Academic Program Development - Reinert, Dana (Association for Continuing Higher Education, 2009)
Institutions of the future must rapidly respond to market demand (i.e., employer needs and student demand) to thrive in today’s educational marketplace. However, developing and implementing new online professional programs in a timely manner challenges even the most nimble and progressive university leaders. When universities have too few faculty to offer a program in an emerging area, collaboration amongst institutions offers a solid opportunity. Inter-institutional collaboration brings unique challenges, but the barriers can be overcome when the participants involved have common goals. Offering an in-demand program that meets significant regional or national needs means that institutions have to learn how to share curriculum and faculty expertise, acknowledge institutional similarities and differences, and recognize barriers and potential pitfalls as the first step to finding workable solutions. By sharing best practices and lessons learned, this paper delineates strategies for determining market demand for academic programs; explains the logic in collaborating across institutions when resources are limited; outlines how to identify appropriate institutional partners and faculty participants; and demonstrates why barriers to collaboration must be judiciously identified then overcome for the creation of sustainable program alliances.
Keywords: Institute for Academic Alliances; Rapid Response Model; Higher Education; Higher Education Alliance; Program Development; Sustainability